2016
DOI: 10.1002/ppap.201600071
|View full text |Cite
|
Sign up to set email alerts
|

Etch Mechanism and Temperature Regimes of an Atmospheric Pressure Chlorine-Based Plasma Jet Process

Abstract: Reactive atmospheric plasma jets containing halogenous compounds are employed as locally acting tools for surface figure shaping or surface modification in ultra‐precision surface machining technologies. In the current study, the interaction between an atmospheric CCl4/O2 containing plasma jet with silicon surface is investigated aiming at elucidating the chemical kinetics of surface reactions. Different process regimes are identified comprising material removal as well as polymeric and oxide layer formation, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 18 publications
0
12
0
Order By: Relevance
“…Various studies investigated the localized etching of silicon [167,168] and of different polymers (e.g., polyethylene, polystyrene, photoresist) [17,169]. Line etching experiments showed that the depth and width of the etched tracks are significantly affected by the sourceto-substrate distance and the scan speed of the source over the substrate (i.e., the etching time) [17,167].…”
Section: Localized Etchingmentioning
confidence: 99%
“…Various studies investigated the localized etching of silicon [167,168] and of different polymers (e.g., polyethylene, polystyrene, photoresist) [17,169]. Line etching experiments showed that the depth and width of the etched tracks are significantly affected by the sourceto-substrate distance and the scan speed of the source over the substrate (i.e., the etching time) [17,167].…”
Section: Localized Etchingmentioning
confidence: 99%
“…At the beginning of the process when the dwell time t is <2 s, the profiles exhibit a near-Gaussian shape, that is usually found for fused silica or Si plasma jet etching. [14] Hence, the near-Gaussian profile represents the reactive particle density distribution always present on the surface. Even if a residual layer is formed, it is thin enough to be penetrated by etching species and the isotropic etching can proceed.…”
Section: Etch Profile As a Function Of Dwell Timementioning
confidence: 99%
“…It has been shown, that reactive plasma jet machining (PJM) provides high flexibility regarding the aimed shape, high process convergence, and avoidance of subsurface damage (SSD) due to the chemical nature of material removal. For this technique, a multicomponent nonthermal chemically reactive plasma jet is applied . The active particles, which are created by pulsed microwave power, react with the solid surface and form volatile compounds, and a local dry etching process takes place .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was shown that the excitation caused by APPJ can be induced by RF or microwave power. The interaction of APPJ with substrates have been experimentally [7][8][9] and theoretically [10] investigated. It has been demonstrated that APPJ processing can be used to etch a variety of different materials such as Si [11], technical glass [12], and SiC [13].…”
Section: Introductionmentioning
confidence: 99%